Economic and social condition of young people in Guanacaste, Costa Rica: A view from the National Census of Population and Housing 2011 - Jiménez Torres, Jairo (2017)
Guanacaste, a province, located in the northwest of Costa Rica, was historically a territory of expulsion of migrants to the rest of the country, mainly to the Central Valley and Caribbean banana plantations. However, since the beginning of the 21st century, the situation began to change and Guanacaste gradually became a province that attracts people despite the fact that the lack of employment opportunities is still recurrent. This study portrays the economic and social situation of young people between 25 and 29 years old and its relationship to the levels of education, employment, illiteracy, migration and economic activity in each canton of the province.